A percepção masculina da violência no contexto dos relacionamentos afetivo-sexuais e seus recortes interseccionais - Giorgini, Maximiliano Pablo (2024)
Gender violence is a circumstance described by some authors as one of the most democratic social phenomena that plague contemporary societies. It is an event present in all social segments that does not distinguish race, ethnicity, religion, age groups, social classes or any other social marker of difference. It is in this context that our research is inserted, which is a study on male perceptions of violence that occur from cisgender heterosexual affective-sexual relationships. Our general objective was to analyze the reflections and practices that construct and develop cisgender men, belonging to the popular sectors, arising as a result of these relationships, using the Recife neighborhood of Água Fria as a unit of empirical analysis. The theoretical-methodological path of the work was carried out based on an interpretative, intersectional and decolonial socio-anthropological approach, of an ethnographic nature, in this way, we used the resources of the qualitative research method, such as semi-structured interviews and participant observations. Fieldwork was carried out simultaneously with information regarding research that addresses issues similar to ours, seeking a reflective dialogue between these investigations and our work. Among the findings that we consider relevant are, firstly, the fact that for our study subjects, the affective-sexual relationships constructed today are characterized in pejorative ways, in relation to relationships conceived in past times, which are described positively and romanticized; secondly, that the ways of meaning masculinity and femininity in these contexts continue to be in accordance with traditional paradigms, where each gender develops specific functions. Men are the providers of family resources and women take care of household chores; and finally, the third fact that we consider relevant in this work is that for our interviewees, violence in affective-sexual relationships is a two-way phenomenon, characterized by physical, verbal and psychological aggression that comes from both genders.